Advancing social prescribing in Singapore: an update on progress - Jojo Qian Hui Nah; Sharna Si Ying Seah; Lian Leng Low; Kheng Hock Lee (Elsevier, 2024)
Summary: In 2019, SingHealth Community Hospitals (SCH) introduced Social Prescribing (SP) program to support patients in transitioning back to the community after hospitalization, which involves personalized care plans developed by Wellbeing Coordinators (WBCs) to connect patients with relevant community resources. With the recent launch of the nation-wide 'Healthier SG' initiative, a population health strategy in Singapore aimed at enabling individuals to prevent and manage chronic diseases, it is important to provide an update on our program's recent developments. This includes creating a living asset map, updating outcome assessment tools, organizing training sessions to enhance the skills SP practitioners, and establishing the Singapore Community of Practice in Social Prescribing (SCOMP).